CT characteristics of intraventricular oligodendrogliomas. - Dolinskas, C A; Simeone, F A (American Journal of Neuroradiology, 1987)
Intraventricular oligodendrogliomas are a rare subset of oligodendrogliomas. Analysis of the clinical and CT characteristics of 11 cases in the literature and eight new examples revealed specific radiographic features, which included the presence of an anterior, midline mass within the lateral ventricles composed of clumped calcifications within a dense, enhancing matrix. Hydrocephalus is a constant feature, and these tumors present with signs of increased intracranial pressure. Eighteen of the 19 cases were benign and all were pure oligodendrogliomas, without admixture of other cellular elements. Intraventricular oligodendrogliomas grow slowly and are associated with prolonged survival but, due to their location, are difficult to remove and frequently require shunting. Subsequently developing symptoms, including herniation and death, are more frequently associated with complications related to hydrocephalus than with tumor growth. Intraventricular oligodendrogliomas can be distinguished from other intraventricular lesions by fairly specific CT characteristics. The ability to recognize them is helpful in prognosis, and awareness of associated complications related to hydrocephalus may assist in the long-term survival of affected patients.